QRIS ACCEPTANCE COMPARISON BETWEEN BATAM CITY AND SAMPIT CITY - Pratama, Jimmy; Alexander, Kevin; Simanjuntak, Fredian (Jurnal TAM (Technology Acceptance Model), 2023)
The emergence of digital payment technology services or Quick Response Code Indonesian Standard (QRIS) digital transactions has brought rapid changes to the way we as a society transact. This research aims to find out what influences or factors make people use QRIS, especially in Batam City and Sampit City, by applying the Technology Acceptance Model (TAM) research model. This research uses a quantitative approach method and uses the SPSS 25 system to analyze the data that has been obtained, and the variables used are Perceived Ease of Use, Perceived Usefulness, System Quality, Information Quality, Service Quality, these variables will be tested against the variables User Satisfaction to find out what factors influence customer satisfaction using QRIS. This research shows differences in results and public perceptions between the two cities, but also similarities in understanding of the advantages of QRIS. There for we can conclude that two different cities have a different perspective.